Combining urban wastewater treatment with biohydrogen production: An integrated microalgae-based approach - Batista, Ana Paula (2015)
The aim of the present work was the simultaneous treatment of urban wastewater using microalgae and the energetic valorization of the obtained biomass. Chlorella vulgaris (Cv), Scenedesmus obliquus (Sc) and a naturally occurring algal Consortium C (ConsC) were grown in an urban wastewater. The nutrient removals were quite high and the treated water fits the legislation (PT Dec-Lei 236/98) in what concerns the parameters analysed (N, P, COD). After nutrient depletion the microalgae remained two more weeks in the photobioreactor (PBR) under nutritional stress conditions, to induce sugar accumulation (22–43%). The stressed biomass was converted into biohydrogen (bioH2), a clean energy carrier, through dark fermentation by a strain of the bacteria Enterobacter aerogenes. The fermentation kinetics were monitored and fitted to a modified Gompertz model. The highest bioH2 production yield was obtained for S. obliquus (56.8 mL H2/gVS) which was very similar when using the same algae grown in synthetic media.